2011
DOI: 10.1634/theoncologist.2011-0108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Borrelia Burgdorferi Infection in a Series of 98 Primary Cutaneous Lymphomas

Abstract: Borrelia burgdorferi has been variably associated with different forms of primary cutaneous lymphoma. Differences in prevalence rates among reported studies could be a result of geographic variability or heterogeneity in the molecular approaches that have been employed. In the present study, we investigated the prevalence of Borrelia burgdorferi sensu lato DNA in diagnostic tissue samples from fresh cutaneous biopsies of 98 primary cutaneous lymphomas and 19 normal skin controls. Three different polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 25 publications
(19 reference statements)
1
54
0
11
Order By: Relevance
“…12 In analogy with geographic incidence variations of CP positivity in OAMZL, endemic as well as nonendemic regions have been defined for this pathogen. Areas seen as endemic, such as the Scottish Highlands or Austria, have demonstrated up to 40% Borrelia infection in cutaneous marginal-zone lymphomas, 12,27 whereas in a large Italian series by Ponzoni et al, 28 no association was observed. In addition, a series of 60 cases of primary cutaneous marginal-zone lymphoma collected in Germany, Asia, and the United States found no evidence for Borrelia infection.…”
Section: Cutaneous Malt Lymphomamentioning
confidence: 93%
“…12 In analogy with geographic incidence variations of CP positivity in OAMZL, endemic as well as nonendemic regions have been defined for this pathogen. Areas seen as endemic, such as the Scottish Highlands or Austria, have demonstrated up to 40% Borrelia infection in cutaneous marginal-zone lymphomas, 12,27 whereas in a large Italian series by Ponzoni et al, 28 no association was observed. In addition, a series of 60 cases of primary cutaneous marginal-zone lymphoma collected in Germany, Asia, and the United States found no evidence for Borrelia infection.…”
Section: Cutaneous Malt Lymphomamentioning
confidence: 93%
“…80 However, other studies, including those from regions where Borrelia is common, have not confirmed this finding. 81,82 PCMZL presents as solitary or multiple papules/nodules most often in the upper extremities, and is usually not seen in the head and neck. Plasmacytoid differentiation is common.…”
Section: Primary Cutaneous Marginal Zone Lymphomamentioning
confidence: 99%
“…In certain areas of Europe, PCMZL is rarely associated with Borrelia burgdorferi infection, but this link has not been found in PCMZL from Asia and the United States. [87][88][89] In plasma cell predominate variants (primary cutaneous plasmocytoma, immunocytoma), other differential diagnoses have to be considered. Secondary cutaneous plasmocytoma could be excluded by staging procedures.…”
Section: Histologymentioning
confidence: 99%